Quo Vadis of Reputation Delict After Constitutional Court Decision Number 76/PUU-XV/2017 - et al., Seno Wibowo Gumbira (International Journal of Advanced Science and Technology, 2019)
Since 2009 until now there have been 30 cases that were tried by the Court with the use of Article 27 paragraph (3) of Law Number 19 of 2016 concerning Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions. The various cases raised opinions from some people who considered the articles on the offense of defamation contrary to the spirit of reform that upheld freedom of opinion and expression. Reputational offenses after the Constitutional Court Decision Number 50 / PUU-VI / 2008, Constitutional Court Decision Number 2 / PUU-VII / 2009, Constitutional Court Decision Number 5 / PUU-VIII / 2010, Decision of the Constitutional Court Number 31 / PUU-XIII / 2015 and Decision of the Constitutional Court Number 76 / PUU-XV / 2017 concerning Testing of Law Number 19 of 2016 concerning Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions of the 1945 Constitution of the Republic of Indonesia. with one of the points being making changes in Article 27 paragraph (3) of the ITE Law and reducing criminal threats in 2 (two) provisions.